1991
DOI: 10.1002/abio.370110303
|View full text |Cite
|
Sign up to set email alerts
|

Atp‐Dependent gold accumulation by living chlorella cells

Abstract: An effect of the Aii(II1) energy dependent concentration has been discovered by living ChZweZZa cells. The process 11s most intensive within the alkaline interval of pH, fading away in the dark, and is suppressed in the presence of arsenate (C 1 FM), fluorides (C 1 0.01 mM), sodium azide (1 mM), DCCD (10 pM), 2,4-dinitrophenol (0.1 mM). I n the dark the process is stimulated b y BTP (but not by ADP, or AIIP). ATP also neutralizes NaN, effect, but not that of DNP. An energy dependent AulIII) concentration is al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 6 publications
1
13
0
Order By: Relevance
“…Even if we were able to show that this effect works for microparticles, it is completely unrealistic for nanoparticles. Reduction in size by at least 10-fold -as seen in the experiments by Pohl's group and in those by the Ukrainian group [27][28][29][30][31][32][33][34][35][36] -would require an electric field that was 10 times stronger to capture the nanoparticles. It is impossible to imagine cells emitting an electric field with a strength around 500 V/cm.…”
Section: Micro-dielectrophoresismentioning
confidence: 97%
See 3 more Smart Citations
“…Even if we were able to show that this effect works for microparticles, it is completely unrealistic for nanoparticles. Reduction in size by at least 10-fold -as seen in the experiments by Pohl's group and in those by the Ukrainian group [27][28][29][30][31][32][33][34][35][36] -would require an electric field that was 10 times stronger to capture the nanoparticles. It is impossible to imagine cells emitting an electric field with a strength around 500 V/cm.…”
Section: Micro-dielectrophoresismentioning
confidence: 97%
“…The results were published in international journals [27][28][29][30][31][32][33][34][35][36]. The cells used in the experiments were representative heterotrophic bacteria, such as Bacillus cereus, Bacillus fascidiosus, Bacillus subtilis, and Pseudomonas iodinum, and microalgae such as Chlorella vulgaris.…”
Section: Reversible Interaction Of Live Cells With Gold Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…The more that can be understood about these organisms (especially bacteria), their specific activities, and their communities, the better the understanding will be of particular "signatures" useful in prospecting. Karamushka et al (1989Karamushka et al ( , 1991 demonstrated that seven genera of freshwater cyanobacteria concentrate Au 3+ from chloride solutions: Nostoc, Spirulina, Phormidium, Anabaena, Microcystis, Anacystis, and Synechococcus (Table 1). The first three of these are especially good concentrators, leaving only about 10% of the available gold in solution.…”
mentioning
confidence: 97%